Inovasi Pemanfaatan Limbah Pupuk Kandang Sapi dan Mikoriza dalam Meningkatkan Hasil Panen Jagung Manis Di Moncok Karya, Ampenan - Astiko, Wahyu; Fauzi, Mohamad Taufik; Sudirman, Sudirman; Ernawati, Ni Made Laksmi; Muthahanas, Irwan (Universitas Mataram, 2025)
The issue of low sweet corn yields and the underutilization of organic waste highlights the need for sustainable agricultural innovation. This community service program aimed to introduce and apply the use of cow manure waste enriched with mycorrhizae to improve sweet corn yields in the